Neuropsychological Assessment of Individuals with Brain Tumor: Comparison of Approaches Used in the Classification of Impairment - Dwan, Toni Maree; Ownsworth, Tamara; Chambers, Suzanne; Walker, David G.; Shum, David H. K. (Frontiers in Oncology, 2015)
Approaches to classifying neuropsychological impairment after brain tumor vary according to testing level (individual tests, domains or global index) and source of reference (i.e., norms, controls and premorbid functioning). This study aimed to compare rates of impairment according to different classification approaches. Participants were 44 individuals (57% female) with a primary brain tumor diagnosis (mean age = 45.6 years) and 44 matched control participants (59% female, mean age = 44.5 years). All participants completed a test battery that assesses premorbid IQ (Wechsler Adult Reading Test), attention/processing speed (Digit Span, Trail Making Test A), memory (Hopkins Verbal Learning Test – Revised, Rey-Osterrieth Complex Figure-recall) and executive function (Trail Making Test B, Rey-Osterrieth Complex Figure copy, Controlled Oral Word Association Test). Results indicated that across the different sources of reference, 86-93% of participants were classified as impaired at a test-specific level, 61-73% were classified as impaired at a domain-specific level, and 32-50% were classified as impaired at a global level. Rates of impairment did not significantly differ according to source of reference (p>.05); however, at the individual participant level, classification based on estimated premorbid IQ was often inconsistent with classification based on the norms or controls. Participants with brain tumor performed significantly poorer than matched controls on tests of neuropsychological functioning, including executive function (p=.001) and memory (p<.001), but not attention/processing speed (p>.05). These results highlight the need to examine individuals’ performance across a multi-faceted neuropsychological test battery to avoid over- or under-estimation of impairment.